1996
DOI: 10.1046/j.1365-2141.1996.272806.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role in growth regulation of tumour necrosis factor receptors p55 and p75 in acute myeloblastic leukaemia cells

Abstract: Tumour necrosis factor (TNF)-alpha exerts multiple effects on human acute myeloblastic leukaemia (AML) cells in vitro, including (1) synergistic stimulation of proliferation with interleukin-3 (IL-3) and granulocyte-macrophage colony-stimulating factor (GM-CSF); (2) inhibition of granulocyte-CSF (G-CSF) and stem cell factor (SCF)-induced growth; (3) suppression of multiplication of clonogenic leukaemic cells; (4) induction of autocrine growth. Recently, two distinct TNF receptors (TNF-Rs), TNF-Rp55 and TNF-Rp7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The majority of TNF-induced NF-B activation (34), growth inhibition, and suppression of proliferation also resulted exclusively from activation of TNFR1 (31,35). In other studies, TNF-induced apoptotic and cytotoxic effects were mediated almost entirely by TNFR1, with TNFR2 having only a minimal effect (34,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of TNF-induced NF-B activation (34), growth inhibition, and suppression of proliferation also resulted exclusively from activation of TNFR1 (31,35). In other studies, TNF-induced apoptotic and cytotoxic effects were mediated almost entirely by TNFR1, with TNFR2 having only a minimal effect (34,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…19,20 The majority of TNF-induced nuclear factor-kB (NF-kB) activation, 21 growth inhibition and suppression of proliferation also resulted exclusively from activation of TNFR1. 22 Although TNF has a cytotoxic or cytostatic effect when tested with various malignant cell lines, clinical trials in cancer patients have revealed high systemic toxicity of TNF. 23,24 It is at present unclear which of the receptors are responsible for the various effects of TNF, although TNFR1 appears to be the predominant receptor that signals both cytotoxic and inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence suggests that tumour necrosis factor (TNF) is involved in the proliferation of acute leukaemia cells ( Hoang et al , 1989 ; Oster et al , 1989 ; Elbaz et al , 1991a , b; Delwel et al , 1992 ; Carter et al , 1994 , 1996). TNF acts as a pleiotropic cytokine enhancing leukaemic growth ( Hoang et al , 1989 ; Oster et al , 1989 ; Carter et al , 1994 , 1996), inducing the transcription of other proliferation‐relevant cytokine or cytokine receptor genes ( Elbaz et al , 1991a , b; Delwel et al , 1992 ; Vinante et al , 1993 , 1996; Khoury et al , 1994 ; Carter et al , 1996 ) and triggering apoptosis ( Elbaz et al , 1991b ; Delwel et al , 1992 ; Khoury et al , 1994 ; Carter et al , 1996 ).…”
mentioning
confidence: 99%